Penerapan Analisis Roi (Retrun On Investment) Untuk Memprediksi Pendapatan Perusahaan - Hastuti Olivia (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2019)
A company that is advanced and successful today is a company that has predicted for a long time even from the beginning of the establishment of a company against the progress and development of its company by knowing and studying several aspects related to the company ranging from knowing the threat, strategy, development and processing of finance very carefully, related to finance is the heart of the company and that determines the running of the company , if the company's finances are unstable it will be very easy to open up the opportunity of the destruction of the company because it is unable to manage the company's finances so that it is not maximal of the usual operating expenses of the company and the cost of income, it is necessary to predict the company's financials against the ability of income generated by a company using ROI analysis that is the length of the retrun on investmaent, the results obtained by the company appear to produce satisfactory profitability in the next five years so that the company can maximize input and output to the company's revenue.